Thalloid Liverworts (Marchantiopsida) of Sri Lanka - Ruklani, N. C. Sumudu; Rubasinghe, Sumudu C. K. (Phytotaxa, 2022)
A comprehensive taxonomic treatment of the thalloid liverworts of Sri Lanka is presented based on specimens collected from throughout the country covering all possible geographical localities. Eight families, nine genera, and seventeen species of complex thalloid liverworts and four families, six genera and seven species of simple thalloid liverworts are described from Sri Lanka. Taxonomic keys, descriptions, along with notes on ecology and distribution, and taxonomic illustrations are provided for all the taxa recognized. Plagiochasma appendiculatum Lehm. & Lindenb., Riccia crispatula Mitt., and Fossombronia cristula Austin, are reported as new to Sri Lanka.